2019
DOI: 10.1002/jia2.25414
|View full text |Cite
|
Sign up to set email alerts
|

What impact could DMPA use have had in South Africa and how might its continued use affect the future of the HIV epidemic?

Abstract: Introduction Some studies suggest that use of the injectable contraceptive depot medroxyprogesterone acetate (DMPA) may increase susceptibility to HIV infection. We aim to determine the influence that such an association could have had on the HIV epidemic in South Africa. Methods We simulate the heterosexual adult HIV epidemic in South Africa using a compartmental model stratified by age, behavioural risk group, sex, male circumcision status and contraceptive use. We model two possible scenarios: (1) The “With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In this modelling study, we used five well described existing HIV models to estimate the impact of different disruptions to HIV prevention and treatment services as a result of the COVID-19 pandemic on HIV-related mortality and incidence. These models were Goals, 10 Optima HIV, 11 HIV Synthesis, 12 an Imperial College London Model, 13 and Epidemiological MODeling software (EMOD). 14 This study arose from discussions within an ad hoc group composed of the authors and other individuals (listed in the Acknowledgments).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this modelling study, we used five well described existing HIV models to estimate the impact of different disruptions to HIV prevention and treatment services as a result of the COVID-19 pandemic on HIV-related mortality and incidence. These models were Goals, 10 Optima HIV, 11 HIV Synthesis, 12 an Imperial College London Model, 13 and Epidemiological MODeling software (EMOD). 14 This study arose from discussions within an ad hoc group composed of the authors and other individuals (listed in the Acknowledgments).…”
Section: Methodsmentioning
confidence: 99%
“…Each model is based on information provided by a wide array of previous studies, as has been described previously. 10 , 11 , 12 , 13 , 14 Importantly, the models make assumptions relating to effects of ART interruption that account for the fact that immune recovery during ART tends to be lost quite rapidly after interruption of treatment. These assumptions are based on, for example, empirical observations 15 , 17 that showed a median loss of 187 CD4 cells per μL after ART interruption and 25% of people have a loss of more than 317 cells per μL in 2 months.…”
Section: Methodsmentioning
confidence: 99%
“…A recent modeling paper concluded that if there is a 20% increased risk of HIV-1 acquisition associated with DMPA-IM use in girls and women, compared with no associated increased risk for DMPA-IM, this could have substantially increased the scale of the HIV epidemic in South Africa, affecting not only the users of DMPA-IM but also their male partners and the wider population. 33 This article highlights the importance of carefully considering the future consequences of contraceptive policy choices, even for increased HIV risks of 20%.…”
Section: What Do the Echo Results Tell Us About Relative Hiv Risk Formentioning
confidence: 99%
“…However, some have argued that a lack of statistical significance for a positive interaction in the ECHO trial does not preclude the possibility of some effect of DMPA on HIV acquisition, merely that it reduces the chance of a strong association [8][9][10][11], because the trial was not designed to detect a hazard ratio below 1.5 (and post-trial analyses revealed that an observed HR of 1.3 or above would have been statistically significant, due to higher than expected subject retention and HIV incidence) [12,13]. Furthermore, for ethical reasons, the trial provided a comparison of HIV risk among DMPA users versus users of other existing contraceptives, rather than no contraceptive.…”
Section: Introductionmentioning
confidence: 99%
“…University of Cape Town, Cape Town, South Africa;8 Aurum Institute, Smith JA et al Journal of the International AIDS Society 2020, 23:e25620 http://onlinelibrary.wiley.com/doi/10.1002/jia2.25620/full | https://doi.org/10.1002/jia2.25620…”
mentioning
confidence: 99%